BETA TESTING FOR INCREASED ACCURACY AND IMPROVED PERFORMANCE OF THE INDONESIAN TSUNAMI EARLY WARNING APPLICATION (Ina-TEWA) - Madlazim; Tjipto Prastowo (Science of Tsunami Hazards, 2019)
Beta testing is a final stage for product examination following a series of product development. Regarding this, beta testing performed for an increased accuracy of Indonesian tsunami early warning application (Ina-TEWA) was applied to real conditions of Indonesian earthquakes with magnitudes of 6.0 or greater that occurred during a time period from January 1, 2018 to July 1, 2019. This stage was conducted in real-time for use of tsunami early warnings officially managed by Centre for Research and Development, The Indonesian Agency for Geophysics, Climatology and Meteorology (BMKG). It is frequently preceded by a series of preliminary tests known as alpha testing usually designed only for laboratory-scaled examination that is limited and offline. While implemented in real-time tsunami warnings, beta testing is considered as examination of acceptance given by and hence direct feedback from users. The launch for this tsunami early warning application is of great importance in the sense that it measures directly tsunami parameters from the earthquake source. The main aim of this stage is to identify possible errors, if any, and to make them the errors minimum for an increased accuracy in tsunami assessment to a maximum value possible. Based on beta testing applied to 35 events during the time period examined here, it was merely 7 errors occurred and found for tsunami false warnings. It follows that the Ina-TEWA prediction for accurate tsunami warnings reaches to a value of 80% or false warnings by this application remains relatively high of 20%. Therefore, tsunami early warning application for future use requires a further increase in terms of accuracy.